Autoconsciência corporal em estudantes de música: avaliação e intervenção - Subtil, Marina Medici Loureiro (2016)
Due to their physical, cognitive and affective demands, learning the musical performance is perhaps one of the most complex human tasks whose boundaries are not yet able to point out in great detail. Studying an instrument involves a multifaceted and multidimensional human experience, with direct impact on the health of that studying. The health of the musician has been a theme investigated by different areas of knowledge, pointing between them, their relationship to physical and psychological processes of health and illness of this professional class. Among the phenomena that make up the health of musicians, we study the most common injuries, the causes associated with the appearance of the lesions and the same treatment tools. Bodily self-awareness appears as a variable cross all these phenomena indicated. It is considered as hypothesis in studies of different areas that individuals with better awareness and perception of the body tend to suffer less from illnesses of neuromusculoskeletal order. Thus, the overall objective of the research is to investigate the body self in university music students and its relation to the prevention and/or appearance of neuromusculoskeletal injuries related to instrumental practice. The research had mixed character and was conducted in two stages. The first is related to the creation and validation of a qualitative evaluation tool for body selfawareness and ergonomic aspects of music students, the Aergo-AutoConMusi. 415 students from undergraduate and bachelor's degree in music from different universities of Brazil participated in this phase, enrolled in all periods. The first phase resulted in two studies: the first one shows the overall evaluation of the results of the Occupational Health music students and the second one presents the development process and instrument validation. The AergoAutoConMusi validation phase resulted in three scales: a range of body self-awareness; a perception of pain scale and finally a scale preventive aspects. The second phase of the research is refered to the clinical trial uncontrolled, driven by an intervention through the Pilate’s concept and lectures on health musician. The intervention was made through the elective course health of musician, with 15 enrolled students of both sexes, aged 19-44 years, mean 26 years. The subject of the meetings were weekly, lasting three hours. Students were grouped in three per class, according to their schedule availability. The intervention phase showed qualitative and quantitative aspects of the implementation of course health of musician. The increase of some physical and behavioral aspects involved with body self-awareness can be observed both by applying the Aergo-AutoConMusi as the reports of the participants. The understanding of the body and specific training of body and behavioral skills in performance made possible in this thesis the reduction of pain complaints and the improvement in some aspects (pain perception, ergonomic aspects of music making) body self-awareness measured by the instrument. We conclude with the results of this thesis, that the body self-awareness in musicians can be based on three dimensions: body self-awareness and the perception of pain; body self-awareness and ergonomic aspects of music making and body self-awareness and preventive health components of the musician. The body's relationship to pain, body posture in performance, behavior of prevention and care in health, to improve and adjust through teaching and bodily experiences specific to the health of the musician, focused on aspects that guide the body self-awareness. For it is a multifactorial phenomenon, body self-awareness in musicians is evident as exploratory field and requires the health participation of different professionals who can contribute to their assessment and their understanding as well as the creation and implementation of programs aimed its improvement in different musical activities.